El debate europeo sobre la flexiseguridad: algunas lecciones para el sur - Vidal Bermúdez, Álvaro (2012)
The present article analyzes the emergence and evolution of flexisecurity strategy in the European context, different conceptualizations, their effects regarding the protective function of labor law and lessons that can be extracted from previous experiences in Latin America and particularly Peru concerning the subordination of social and labor policies on the policies of employment generation.